2010
DOI: 10.1051/0004-6361/200912921
|View full text |Cite
|
Sign up to set email alerts
|

Spectral evolution of bright NS LMXBs withINTEGRAL: an application of the thermal plus bulk Comptonization model

Abstract: Aims. The aim of this work is to investigate in a physical and quantitative way the spectral evolution of bright neutron star low-mass X-ray binaries (NS LMXBs) with special regard to the transient hard X-ray tails. Methods. We analyzed INTEGRAL data for five sources (GX 5-1, GX 349+2, GX 13+1, GX 3+1, GX 9+1) and built broad-band X-ray spectra from JEM-X1 and IBIS/ISGRI data. For each source, X-ray spectra from different states were fitted with the recently proposed model compTB. Results. The spectra have bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Mainardi et al 2010;Seifina & Titarchuk 2012;Piraino et al 2012). We find a neutral column density (NH) of ∼ 1.6 × 10 22 cm −2 , using the abundances of Anders & Grevesse (1989).…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Mainardi et al 2010;Seifina & Titarchuk 2012;Piraino et al 2012). We find a neutral column density (NH) of ∼ 1.6 × 10 22 cm −2 , using the abundances of Anders & Grevesse (1989).…”
Section: Spectral Analysismentioning
confidence: 99%
“…van den Berg et al (2014) identified a counterpart of GX 3+1 in the near-infrared (NIR) with a Ks=15.8 +/-0.1 mag suggesting that the donor star is not a late-type giant and that the NIR emission is dominated by the heated outer accretion disc. Spectral analyses of the source showed that its X-ray spectrum can be described by a model comprising of a soft blackbody component, most likely associated with the accretion disc, and a comptonizing component, produced by an optically thick electron population located close to the NS boundary layer (Mainardi et al 2010;Piraino et al 2012;Seifina & Titarchuk 2012). Seifina & Titarchuk (2012), using all the Rossi X-ray Timing Explorer (RXTE) and BeppoSAX data, showed that the comptonizing component is quite stable suggesting that the energy release in the transition layer between the accretion disc and the NS dominates over the energy release in the accretion disc.…”
Section: Introductionmentioning
confidence: 99%
“…According to Paizis et al (2006) and Mainardi et al (2010), the relative importance of thermal versus dynamical (bulk) Comptonisation is a very effective parameter in modelling the variety of NS-LMXBs spectral states and the state transitions in individual sources. In their scenario, LHS are characterised by a large height scale and radially extended hot electron plasma able to screen, to a distant observer, the bulk Compton amplification effects (occurring very close to the NS).…”
Section: Double-seed Models and Extended Coronasmentioning
confidence: 99%
“…Therefore a double-seed Comptonised emission (like the one we propose for GS 1826−238) is easier to reconcile with the above framework than the classic eastern-like model, as it implies a more radially extended corona. In fact, this picture of a (relatively luminous) LHS smoothly evolves, with increasingṁ and reduced coronal height scale, into the intermediate state picture of Paizis et al (2006) and Mainardi et al (2010).…”
Section: Double-seed Models and Extended Coronasmentioning
confidence: 99%
“…For modeling the spectra with XSPEC 12, we used the COMPTB model recently introduced by Farinelli et al (2008), and employed to study BeppoSAX spectra of Cyg X-2 in Farinelli et al (2009), and several NS LMXBs in Mainardi et al (2010). COMPTB combines the thermal and bulk motion Comptonization of a seed photon spectrum to create a unified physical model that seeks to explain the spectral evolution of NS LMXBs.…”
Section: Observations Data Reduction and Modelingmentioning
confidence: 99%